Clinical implications of concomitant variations of the testicular, suprarenal and renal veins: A case report - (:unkn) unknown (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2002)
Multiple venous anomalies have been observed during dissection of the posterior abdominal wall in a 65-year-old, white male cadaver. The left testicular and suprarenal veins united inferior to the superior mesenteric artery, coursed anterior to the abdominal aorta and drained into the inferior vena cava (IVC). Further the left renal vein coursed retroaortically and divided into three branches. The superior branch coursed on the vertebral column and drained into the azygos vein while middle and inferior branches drained into the IVC. The right renal vein was double and both drained into the IVC separately. Due to implications for numerous therapeutical and diagnostic procedures in the retroperitoneal region knowledge of these variations could be useful for clinicians in its recognition and protection.
Keywords: testicular vein; suprarenal vein; renal vein-inferior vena cava; azygos vein; lumbar vein; ANATOMY; NUTCRACKER; ANOMALIES; SURGERY